Pathological and aetiological studies on pneumonia of sheep in the konya province - Metin Münir Kıran; Şenay Berkin; Osman Kaya; Zuhal Dinçer (Eurasian Journal of Veterinary Sciences)
In this study, 1083 lungs taken from various breeds of sheep were macroscopically examined at the "Meat and Fishery Organisation Konya Meat Combine". Out of 1083 lungs examined, in 273 cases (25.2 %), macroscopic lesions were detected. Histologically, pneumonias were classified as follows; 1. Catarrhal-purulent bronchopneumonia (0.5 %), 2. Necrotic bronchopneumonia with abscessation (3.2 %), 3. Interstitial pneumonia (1.8 %), 4. Verminous pneumonia (11.8 %), and5. Pulmonary adenomatosis (7.9 %). There was no relationship between isolated microorganisms and the pathological lesions